Literacy of Online Gender Based Violence (OGBV) in Gen-Z: Retno Manuhoro Setyowati - Retno Manuhoro Setyowati (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2023)
Generation Z in Indonesia is the internet user with the highest penetration rate of 99.26% (APJII 2022 data), because they were born in the digital era, In the internet era, the production, consumption and distribution of information on the internet appear like a double-edged knife. On the one hand, it has a positive impact, but on the other hand, useless and uneducative content has emerged. Misuse of information and even digital crimes have also emerged massively, one of which is Online Gender-Based Violence (KBGO) with a crime pattern that is not easy to read, with a variety of modes so that cases have increased by 300% in the last six years (Komnas Perempuan, 2020). This research aims to find out the extent of literacy competence and experience of KBGO in Gen-Z with the research subject of Communication Science students at the University of Semarang. Using the concept of digital literacy developed by the Ministry of Communication and Information - Siberkreasi as a basis for analysis, this research uses mixed methods, namely online surveys and phenomenological in-depth interviews. The research found that Gen-Z naturalised KBGO in a joking context and did not take it seriously. Another thing is that the WhatsApp messaging application is on average a medium for spreading pornographic content through text, stickers, emoticons, videos or photos.